Infrastrutture stradali più sicure. Fase I: i criteri XXVI Convegno nazionale stradale - Comitato Tecnico C1, AIPCR (Proceedings e report, 2010)
The monograph is a WRA technical notebook that will be distributed on the occasion of the 26th WRA National Convention to be held in Rome on 27-30 October 2010. The notebook was prepared by the members of the Technical Committee C1 of the WRA, made up of Academics, Road Management Bodies and Planners and chaired by Prof. Domenichini, Professor at the University of Florence. The book is divided into 3 chapters that address three highly topical issues in the field of road infrastructure safety: the European Directive 2008/96/EC on the management of road infrastructure safety, the analysis of the human factor in road accidents and the transition areas to protect the urban sections belonging to the extra-urban roads.